2021
DOI: 10.2147/ndt.s317027
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Fatigue in Subjects Recovered from COVID-19 Infection: A Case–Control Study

Abstract: Purpose Much effort has been directed toward studying COVID-19 symptoms; however, the post–COVID-19 phase remains mysterious. The aim of this work was to conduct a clinical and neurophysiological evaluation of physical and mental fatigue in COVID-19 long-haulers and to study whether markers of COVID-19 severity are able to predict the likelihood of developing postinfectious fatigue syndrome (PIFS) in such patients. Patients and Methods This case–control study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…Elanwar et al ( 11 ) defined participants as patients with post-COVID-19 if they were diagnosed with postinfectious fatigue syndrome (PIFS). In order to fulfill the definition of PIFS, patients had to have persistent fatigue for at least 6 months after recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elanwar et al ( 11 ) defined participants as patients with post-COVID-19 if they were diagnosed with postinfectious fatigue syndrome (PIFS). In order to fulfill the definition of PIFS, patients had to have persistent fatigue for at least 6 months after recovery.…”
Section: Resultsmentioning
confidence: 99%
“…El Sayed et al ( 14 ) used the fatigue assessment scale. Elanwar et al ( 11 ), Townsend et al ( 15 17 ) used the Chalder fatigue scale providing a total fatigue score from 0-4. Scores of 2 or above are regarded as fatigued.…”
Section: Resultsmentioning
confidence: 99%
“…43 Moreover, one study found that PCS survivors with post-infectious fatigue syndrome, a condition highly similar to ME/CFS, had (i) higher scores of physical and mental fatigue, (ii) more abnormal neurophysiological assessments and (iii) more severe acute COVID-19 compared with controls (i.e., COVID-19 survivors without PCS). 47 Another study reported that depending on the diagnostic criteria, 13%-18% of discharged COVID-19 patients developed ME/ CFS at 6-month. 44 Similarly, in another study, 23% of SARS-CoV-2positive persons with no history of fatigue and cognitive dysfunction developed ME/CFS at 6-month.…”
Section: Myalgic Encephalomyelitis/chronic Fatigue Syndrome (Me/cfs)mentioning
confidence: 99%
“…PICOS (population, intervention, comparison, outcome and study designs) criteria were used as the inclusion criteria (see Table 1). Studies were required to fulfill the following five inclusion criteria: (1) MF was observed in participants; (2) studies published in English with the application of MBI, regardless of population characteristics, such as age, gender, and ethnicity; (3) randomized controlled trials (RCTs), non-randomized controlled trials (nRCTs) and non-randomized non-controlled trials (nRnCTs) with two or more groups and single-group trials; (4) MBI was used for intervention; (5) comparison was made without MBI and MF-inducing possibility. The exclusion criteria were as follows: (1) systematic review; (2) medical or neuropsychological studies.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…For example, since the emergence of the COVID-19 pandemic, peoples' mental health has been adversely affected. Studies have reported that people associated with the medical profession, such as nurses and recovered and isolated individuals, are likely to experience MF [1][2][3]. This prevalence of MF has implicated a lot of aspects of daily life.…”
Section: Introductionmentioning
confidence: 99%